2016
DOI: 10.1177/2045125316683151
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of clozapine and other antipsychotics for patients with first-episode psychosis: a cross-sectional survey of early intervention teams

Abstract: The majority of patients were prescribed antipsychotics within the guidelines. EIS was associated with an overall low antipsychotic discontinuation. There was also a short waiting time before clozapine was initiated following patients being accepted into EIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
2
12
1
Order By: Relevance
“…In this retrospective review of referrals to a national immunology centre, we found that individuals with schizophrenia receiving clozapine displayed clinically significant pan-hypogammaglobulinaemia, impaired vaccine responses and disturbed B-cell maturation with a proportion benefitting from IgRT. Consistent with a specific relationship to clozapine use, we observed enrichment of clozapine use among patients with schizophrenia undergoing immunology assessment or requiring IgRT relative to that reported in the wider population by a number of recent studies 4 17 24. The most common feature at referral was a low CG 25.…”
Section: Discussionsupporting
confidence: 81%
“…In this retrospective review of referrals to a national immunology centre, we found that individuals with schizophrenia receiving clozapine displayed clinically significant pan-hypogammaglobulinaemia, impaired vaccine responses and disturbed B-cell maturation with a proportion benefitting from IgRT. Consistent with a specific relationship to clozapine use, we observed enrichment of clozapine use among patients with schizophrenia undergoing immunology assessment or requiring IgRT relative to that reported in the wider population by a number of recent studies 4 17 24. The most common feature at referral was a low CG 25.…”
Section: Discussionsupporting
confidence: 81%
“…38 The prevalence of clozapine use in the present study is lower than that in an Irish study reporting a prevalence of 16.3% in patients with first-episode schizophrenia 15 but higher than that in America (0.7%), 16 Spain (2.4%), 39 Singapore (4.3%) 14 and UK (9.7%). 9 Several reasons may account for the higher prevalence of clozapine use in the present study. First, clozapine is among the least expensive antipsychotics in China, as a 400 mg clozapine dose costs less than 1 dollar.…”
Section: Discussionmentioning
confidence: 72%
“…However, a portion of patients with schizophrenia manifest treatment resistance to antipsychotics at the onset of schizophrenia, and the reported prevalence of TRS in patients with first-episode schizophrenia widely varies from 8.4% to 34%. [8][9][10][11][12] However, clozapine was commonly underutilized, and its initiation was delayed among patients with first-episode schizophrenia. [12][13][14][15] Approximately 0.7%-26.6% of patients with first-episode schizophrenia received clozapine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the Spanish study in 2016, the frequency of prescribing AMT was slightly higher than our finding (69.2%), but the frequency of prescribing FGA as a monotherapy was only 3.7% 43 . In the British study from 2017, the frequency of prescribing AMT was 77.3%, with FGA accounting for 3.9% of prescriptions 44 . These differences in the findings could mean a better adherence to the recommendations of GCP in developed countries, which can be explained by the non-binding nature of our guide and the lack of regulatory bodies that would monitor the prescribing practice, which is mandatory in the Western countries 45 .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, most guidelines, including Serbian, for the people with the FPE recommend the mandatory administration of SGAs in lower and moderate doses in order to ensure the best adherence and prevention of relapses after stabilization of symptoms in the acute phase of treatment 16,18,19 . Four re- cent cohort studies from the United States, Finland, Spain and the United Kingdom examined the patterns of prescribing AP in the FPE, so that they can serve for international comparisons 25,[42][43][44] . In our study, a total of 66.1% of subjects were treated with antipsychotic monotherapy with a total of ten antipsychotics (five from the class FGAs and SGAs).…”
Section: Discussionmentioning
confidence: 99%